Manganese Deposits in the Neighbourhood of Tamworth, New South Wales (The Australasian Institute of Mining and Metallurgy, 1962)
Deposits of manganese oxides and silicates in the Tamworth area were re-examined. The major deposit at Danglemah consists chiefly of rhodonite and the rare silicate tephroite. It is considered that the manganese was deposited with the original sediments, the silicates being formed later during the intense folding and low-grade metamorphism of the enclosing rocks.INTRODUCTIONMany small deposits of manganese oxides and silicates occur along a belt of eastern New South Wales and Queensland.Some fifty occurrences, most of which have been subject to mining activity, were described by Lloyd (1943) and some of this information was summarized by Knight (1947). The ores have been mined on a small scale since 1884. Small supplies of battery grade ore were won from a number of deposits, while larger quantities of metallurgical grade were sold to the steel industry. Maximum production was in 1918, when 6,500 tons were mined.The siliceous nature of many of the ores and their occurrence in the neighbourhood of granite batholiths led earlier investigators to consider the deposits to be of hydrothermal origin, associated with the granite intrusions. The present work questions this viewpoint.In this investigation, three of the chief deposits in the Tamworth area were seen. These were at Danglemah, which is being mined at present, and Mount Jasper and Manganese Mountain, which were mined in the past. The Danglemah mine is the most accessible and yields the best material...